MEMERIKAN FUNGSI KONTEKS SITUASI DALAM PERSPEKTIF PRAGMATIK SIBER - R. Kunjana Rahardi (Linguistik Indonesia, 2022)
This research aims at describing the manifestation of situational contexts in the culture-specific pragmatic phenomena in the perspective of cyber-pragmatics. This is a qualitative research. The research data sources are authentic texts taken from social media captions containing situational contexts. The research data are elements of situational contexts found in the authentic utterances in social media captions. The research data are gathered using the observation method employing the note-taking technique. The gathered data are classified and typified to generate types of data in details. Then, the data are analyzed using the distributional analysis method and the pragmatic identity method. The distributional analysis method is used to analyze the linguistic dimensions of this research, while the pragmatic identity method, particularly extra-lingual identity, is applied to analyze the extra-linguistic dimensions of this research. The preliminary research results show that the situational contexts proposed by Geoffrey N. Leech need to be reinterpreted and redefined to adjust to the development of current situational contexts. Situational contexts are inseparable from the digital information technology because language is not immune from the impact of the technology development. Ignoring situational contexts in the perspective of cyber-pragmatics in studying language phenomena will not yield proper research results in the present-day contexts. Â Keywords: cyberpragmatics, culture-specific pragmatics, konteks situasi, informasi digital